COMPARATIVE ECONOMIC ANALYSIS: EURO-ADOPTING VERSUS NON-EURO EU COUNTRIES - Nicoleta PANAIT; Mădălina RĂDOI (Challenges of the Knowledge Society)
This paper analyses the macroeconomic evolution of the EU member states that have adopted the euro, compared to those that continue to use national currencies, with a specific focus on the Central and Eastern European countries during the period 2018–2024. Using a mixed-methods approach and data provided by Eurostat, the European Central Bank (ECB), and the International Monetary Fund, we examined a series of key indicators: interest rates, inflation, GDP per capita, public debt, and foreign direct investment (FDI). Eurozone countries benefit from significant macroeconomic advantages, largely due to access to monetary tools such as the Pandemic Emergency Purchase Programme (PEPP) and the Transmission Protection Instrument (TPI), both implemented by the ECB. These mechanisms helped stabilize financial markets, reduce interest rate volatility, and ensure effective transmission of monetary policy, especially during crises like the COVID-19 pandemic. PEPP, launched in March 2020, aimed to mitigate serious risks to the euro area economy by purchasing public and private sector securities. TPI, introduced in 2022, supports monetary policy transmission by allowing the ECB to purchase sovereign bonds from member states that meet certain criteria, helping to prevent unjustified market fragmentation. In contrast, non-euro countries like Romania and Poland, without access to these tools, have experienced more severe inflation and higher borrowing costs. The results show that the position of countries after joining the euro area varies from one state to another; however, signs of stabilization in macroeconomic indicators can be observed following euro area accession.